(untitled) (Fiep Bulletin - online, 2014)
Complexity is the systemic approach to phenomena. It strengthens the interaction between each part and the whole, leaving behind the reductionism that has been permeating most science investigation fields, giving place to creativeness, turning selforganizing processes and impossible (“UNPREDICTABLE”) behaviors viable. This study aims to present high profile sports games as a complex adaptative system based upon the high profile teams that integrate this system, following the reference mainframe proposed by Axelrod & Cohen. It is important to notice that three essential processes feed sports games as complex adaptative systems: variability, interaction and selection. These processes offer an intertwined concepts set that generate productive actions in the system. This system cannot be fully understood and controlled by its complexity, but it offers opportunities and resources to notice its structural bases and allow its development through pondered intervention. Complex adaptative systems are considered in terms of agents populations that, through strategies and artifacts, interact among themselves and with the environment in a purposeful way or not. These agents (athletes, referees, coaches, supporters) may be in evidence during a sport game, while others (roupeiro, physical therapist, physical trainer, nutritionist…) may not be seen by the general public, but, by their interaction capability and in their specific strategies fulfillment, are responsible for a team achievement degree in a specific game or competition.